Intensive blood pressure management for ischemic stroke patients following endovascular thrombectomy: a meta-analysis of randomized controlled trials - Shenglei Jiang; Yitao Zhou; Yangbin Zhou; Ganying Huang (BMC Neurology)
Abstract Objective This meta-analysis aimed to determine the potential benefits of intensive blood pressure management in ischemic stroke patients who have undergone endovascular thrombectomy (EVT). Methods We comprehensively searched all relevant studies published before August 23, 2024, using multiple databases, including Cochrane Library, Embase, PubMed, Web of Science and China National Knowledge Infrastructure (CNKI) and Wangfang. The primary outcomes were favorable outcomes at 90 days (mRS score = 0–2), while the secondary outcomes comprised 90-day mortality, incidence of symptomatic intracranial hemorrhage (sICH), and 7-day mortality. Results Six randomized controlled trials studies involving 1752 patients were included. The incidence of 90 days (mRS score = 0–2) score was significant difference between different blood pressure management (RR = 0.81, 95% CI [0.74, 0.89], p < 0.01) with heterogeneity (I2 = 0%, p = 0.52). No significant difference was perceived in the 90-day mortality (RR = 1.16, 95% CI [0.90, 1.48], p = 0.28; I2= 0%, p = 0.89). Additionally, there was no statistically significant difference in the incidence of sICH, (RR = 1.03, 95% CI [0.72, 1.48], p = 0.86; I2= 0%, p = 0.42). There was also no statistically significant discerned in the 7-day mortality (RR = 1.33, 95% CI [0.88, 2.01], p = 0.17; I2= 0%, p = 0.67). Conclusion Our research results suggest that routine standard blood pressure management is more beneficial to the functional independence for patients, a more moderate intensive blood pressure management should be used.